Miniaturized Liquid Metal Composite Circuits with Energy Harvesting Coils for Battery‐Free Bioelectronics and Optogenetics - Rocha, Denis; Lopes, Pedro; Peixoto, Paulo; Almeida, Aníbal; Tavakoli, Mahmoud (Advanced functional materials, 2025)
Over the past years, rapid progress has been made on soft‐matter electronics for wearable and implantable devices, for bioelectronics and optogenetics. Liquid Metal (LM) based electronics are especially popular, due to their long‐term durability, when subject to repetitive strain cycles. However, one major limitation has been the need for tethering bioelectronics circuits to external power, or the use of rigid bulky batteries. This has motivated a growing interest in wireless energy transfer, which demands circuit miniaturization. However, miniaturization of LM circuits is challenging due to low LM‐substrate adhesion, LM smearing, and challenges on microchip‐interfacing. In this article, these challenges are addressed by high‐resolution laser‐assisted micropatterning of biphasic LM composites and vapor‐assisted LM microchip soldering. Through the development of a search algorithm for optimization of the biphasic ink coil performance, micro coils with trace spacing of 50 µm are designed and implemented that can harvest a significant amount of energy (178 mW cm−2) through near field inductive coupling. Miniaturized soft‐matter circuits with integrated SMD chips such as NFC chips, capacitors, and LEDs that are implemented in a few minutes through laser patterning, and vapor‐assisted soldering. In the context of optogenetics, where lightweight, miniaturized systems are needed to provide optical stimulation, soft coils stand out in terms of their improved conformability and flexibility. Thus, this article explores the applications of soft coils in wearable and implantable devices, with a specific focus on their use in optogenetics. A combination of biphasic liquid metal inks, high‐resolution laser patterning, and reversible polymer‐gel microchip integration is presented for fabrication of conformal, and miniaturized stretchable circuits for wearable and implantable bioelectronics. Through optimization of materials and fabrication techniques, miniaturized chip‐integrated patches that integrate ultracompact coils for energy harvesting are developed, for application in optogenetic research.